An Approach to Digitalize the Health Care System of Bangladesh using Smartphone - Md. Kamrul Hossain; Ahmed Imteaj; Kazi Hassan Shakib; Saika Zaman (SISFORMA, 2021)
Health is one of the basic needs of human life. If this need cannot be fulfilled, then nothing can compensate for the loss. Often in Bangladesh, we observe that the economic ability of mass people can hardly ensure proper health care. The poor are being deprived of proper health care and even though the rich class can afford quality health care, but it comes with many compromises with their valuable time and labor. To meet the gap, we thought of a smartphone-based health care system that will assist people, especially the underprivileged, to attain health care easily and effectively. To effectively use the ICT facility that the government and non-government sectors are providing, we made a mobile application that will have several features including online appointment and cabin booking, prescription generator, hospital, and doctor's information displayed along with the suggestion, medicinal and disease information, etc. Since there is a great need for a system that can alarm people of emerging diseases in their area, we made a system to alarm people about that. Moreover, in the world of continuous changes, there is a great need for communication to acquire the latest knowledge. Hence a social network where doctors can discuss cures and medication will be of great benefit. Along with this, the need for continuous observation of medicinal side effects is not negligible. So, we need a proper channel for communication between patient and doctor, especially when a patient encounters some trouble when he takes the pre-scribed medications because of their side effects.